2022
DOI: 10.1038/s41598-022-06615-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of L-type amino acid transporter 1 (LAT1) with the immune system and prognosis in invasive breast cancer

Abstract: L-type amino acid transporter 1 (LAT1), also referred to as SLC7A5, is believed to regulate tumor metabolism and be associated with tumor proliferation. In invasive breast cancer, we clinicopathologically investigated the utility of LAT1 expression. LAT1 expression was evaluated via immunohistochemistry analyses in 250 breast cancer patients undergoing long-term follow-up. We assessed the relationships between LAT1 expression and patient outcomes and clinicopathological factors. Breast cancer-specific survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…SK4 represents is the first iron chelator designed to gain cell entry through the LAT1 transporter exploiting "iron addiction" as well as dysregulated amino acid metabolism. LAT1 overexpression has been associated with poorer patient prognosis, and metastatic tumors, thus limiting iron chelation entry to the LAT1 transporter could be more suited to malignant tumors and could dampen potential side effects associated with iron chelation such as methemoglobinemia and myelosuppression (Yu et al, 2012a;Ichinoe et al, 2015;Ichinoe et al, 2021;Kurozumi et al, 2022). Interestingly, LAT1 is an antiport so while it can allow the entry of amino acids it has no effect on the total amount of amino acids within the cells but can influence the proportions of different amino acids, so SK4 may compete with amino acids for cell entry (Yanagida et al, 2001;Verrey et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SK4 represents is the first iron chelator designed to gain cell entry through the LAT1 transporter exploiting "iron addiction" as well as dysregulated amino acid metabolism. LAT1 overexpression has been associated with poorer patient prognosis, and metastatic tumors, thus limiting iron chelation entry to the LAT1 transporter could be more suited to malignant tumors and could dampen potential side effects associated with iron chelation such as methemoglobinemia and myelosuppression (Yu et al, 2012a;Ichinoe et al, 2015;Ichinoe et al, 2021;Kurozumi et al, 2022). Interestingly, LAT1 is an antiport so while it can allow the entry of amino acids it has no effect on the total amount of amino acids within the cells but can influence the proportions of different amino acids, so SK4 may compete with amino acids for cell entry (Yanagida et al, 2001;Verrey et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We selected LAT1 as the mode of cell entry as LAT1 is commonly overexpressed in cancer including breast, prostate and ovarian (Sakata et al, 2009;Segawa et al, 2013;Kaira et al, 2015;Ichinoe et al, 2021;Kurozumi et al, 2022). Additionally, metastatic tumors tend to have higher levels of LAT1 (Ichinoe et al, 2015;Papin-Michault et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…SLC7A5 mediates Leu uptake in breast cancer and enhances mTORC1 signaling, eventually resulting in aromatase inhibitor resistance 59,60 . Furthermore, SLC7A5 expression is positively associated with tumor size, histological grade, tumor infiltrating lymphocytes (TILs), and programmed death ligand 1 (PD‐L1) while negatively associated with ER and progesterone receptor (PR) in breast cancer 61 . A recent study showed that SLC7A5 was an immune infiltration‐related biomarker and breast cancer patients with high SLC7A5 expression were insensitive to paclitaxel and doxorubicin and had poor prognoses 62 …”
Section: Amino Acid Transporters In Breast Cancermentioning
confidence: 99%
“…The light subunit LAT1 (SLC7A5) ( Scalise et al, 2018 ) is expressed mainly in organs such as the brain, placenta, spleen and testis ( Nakamura et al, 1999 ; Prasad et al, 1999 ). Furthermore, LAT1 is overexpressed in numerous cancer types, e.g., brain ( Nawashiro et al, 2006 ), breast ( Kurozumi et al, 2022 ), gastric ( Ichinoe et al, 2011 ), lung ( Kaira et al, 2008 ), pancreatic ( Kaira et al, 2012 ), prostate ( Sakata et al, 2009 ), renal cell ( Betsunoh et al, 2013 ) and urologic cancer ( Nakanishi et al, 2007 ) (also see ( Wang and Holst, 2015 ) and ( Häfliger and Charles, 2019 ) for LAT1 expression in other tumors), and is used as a pathological factor for an unfavorable prognosis in patients. In such cancer cells, the nutritional uptake of neutral and essential neutral amino acids, and co-regulation of the mammalian target of rapamycin (mTOR) signaling pathway is mediated by the LAT1 transporter ( Nicklin et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%